Qashr dalam kitab Ihya Ulumuddin Rubu’ Ibadah karya Imam Al-Ghazali - Dodi Robiansyah; Ii Rahmanudin (Institut Agama Islam Darusssalam Blokagung, 2023)
Abstract The purpose of the researcher is to find out the Qashr method in the book Ihya Ulumuddin Rubu' Ibadah by Imam Al-Ghazali. As well as Knowing the distribution of Qashr and the meaning of the number contained in Qashr in the book Ihya Ulumuddin Rubu' Ibadah by Imam Al-Ghazali. The method used is the library research method, in which the researcher uses an analytical descriptive method. As for the research steps, determining research data sources, determining research data types, and research data collection techniques with libraries and documentation, as well as for analyzing and processing data, there are stages used in research, such as Data Description Stage, Data Classification Stage Namely the data that has been described, then classified or grouped according to the problem. From the results of the analysis conducted by researchers on the book Ihya' 'Ulumuddin with the Qashr approach, the results of this study state that in the book Ihya' 'Ulumuddin Rubu' Worship from the knowledge chapter to the prayer chapter there are 60 uslub qashr.